Chicago Classification Update (v4.0): Technical review on diagnostic criteria for distal esophageal spasm. Issue 5 (5th March 2021) - Roman, Sabine; Hebbard, Geoff; Jung, Kee Wook; Katz, Phil; Tutuian, Radu; Wong, Reuben; Wu, Justin; Yadlapati, Rena; Sifrim, Daniel
Abstract: Distal esophageal spasm (DES) is defined as a manometric pattern of at least 20% of premature contractions in a context of normal esophago‐gastric junction relaxation in a patient with dysphagia or non‐cardiac chest pain. The definition of premature contraction requires the measurement of the distal latency and identification of the contractile deceleration point (CDP). The CDP can be difficult to localize, and alternative methods are proposed. Further, it is important to differentiate contractile activity and intrabolus pressure. Multiple rapid swallows are a useful adjunctive test to perform during high‐resolution manometry to search for a lack of inhibition that is encountered in DES. The clinical relevance of the DES‐manometric pattern was raised as it can be secondary to treatment with opioids or observed in patients referred for esophageal manometry before antireflux surgery in absence of dysphagia and non‐cardiac chest pain. Further idiopathic DES is rare, and one can argue that when encountered, it could be part of type III achalasia spectrum. Medical treatment of DES can be challenging. Recently, endoscopic treatments with botulinum toxin and peroral endoscopic myotomy have been evaluated, with conflicting results while rigorously controlled studies are lacking. Future research is required to determine the role of contractile vigor and lower esophageal sphincter hypercontractility in the occurrence of symptoms in patients with DES. The role of impedance‐combined high‐resolution manometry also needs to be evaluated.